Interest of Social Representations Theory to grasp coastal vulnerability and to enhance coastal risk management (Interés de la Teoría de las Representaciones Sociales para entender la vulnerabilidad costera y para mejorar la gestión de los riesgos costeros). Issue 1 (2nd January 2020) - Meur-Ferec, Catherine; Guillou, Elisabeth
ABSTRACT: This theoretical paper provides a new perspective on coastal vulnerability analysis by combining geography and psycho-social approaches. Most studies on perceptions of coastal risks report that people who are exposed have a low level of perceived vulnerability (they are not anxious), strong place attachment (they love their living place and want to live close to the sea) and are resistant to changes in adaptation strategies (they do not want to move away). For natural scientists and managers, these findings usually appear as paradoxes that enhance vulnerability and lead to these people being labelled 'irrational', 'in denial', 'uninformed' or 'uneducated'. Based on our long-term studies among coastal inhabitants in France, we believe that using Social Representations Theory (SRT) in this context enables us to go beyond these preconceived and individual-centred ideas towards a more contextualized view. This position extends theoretical risk/vulnerability research and is applicable to coastal risk management.